FIGURATIVE LANGUAGE IN LINKIN PARK’S SONG LYRICS IN SEEING CHESTER’S SUICIDE IDEATION - Noselya, Esteralda Rafaela (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
A way to understand an author is through an understanding of his works. In this case, Linkin Park has done many albums, but there is one particular year that creates questionable relations. In year 2017, Linkin Park’s lead singer died in suicide attempt in the same year the album “One More Light” was released. There might be relations between the ten songs of the album and Chester’s suicide act. Therefore, the focus of this study is to understand Chester Bennington’s suicide act through his suicide ideation by analyzing Figurative Language in ten of the 2017 released songs by Linkin Park under Semantics study. In which, the writer did the study through library research, qualitative research method, and descriptive approach while doing observation to collect the data. Out of the ten songs analyzed, 56 data of Figurative Language which divided into 12 categories were found. The result amounts show that Figurative Language could uncover many invisible meanings that the author used to describe their feelings, ideas and thoughts. In other hand, through the analysis of Figurative Language, 31 data of the 3 factors of Suicide Ideation were found. This result shows that Chester had a strong suicide Ideation which further leads to his suicide act.